Identifikasi Perkembangan Anak Berdasarkan Kejadian Stunting Usia dibawah 5 Tahun - Ihsan, Alfisyahr Nindya Maqbul; Arfah, Arni Isnaini; Mulyadi, Farah Ekawati; Darussalam, Andi Husni Esa; Darma, Sidrah (Journal of Telenursing (JOTING), 2024)
This study aims to determine the incidence of stunting in children under 5 years old at the Salotungo Soppeng Health Center, as well as to determine the development of stunting children under 5 years old at the Salotungo Soppeng Health Center. The method used in this study is a descriptive research to identify child development based on KPSP in the incidence of stunting in children under 5 years old. The results of the study showed that the incidence of stunting in children under 5 years old at the Salotungo Soppeng Health Center amounted to 62 children. It was found that the most common incidence of stunted children with developmental disorders, especially at the age of 30 months and male sex as many as 20 children (32.2%). The conclusion in this study is that stunted children at the Salotungo Soppeng Health Center, especially men, have a high risk of developing developmental disorders at the peak age of 30 months. Biological, genetic, and suboptimal food transition factors play a role in stunting and developmental delays. Early intervention is urgently needed to prevent long-term impacts. Keywords: Child Development, Stunting, Toddler